2014
DOI: 10.1186/1465-9921-15-20
|View full text |Cite
|
Sign up to set email alerts
|

Impact of gender on COPD expression in a real-life cohort

Abstract: Reports regarding gender-related differences in COPD expression have provided conflicting results. In the French Initiatives BPCO real-world cohort, which contained 688 patients (146 women) when data were extracted, women were matched with men (1:3 ratio: n = 107:275) on age (5-year intervals) and FEV1 (5% predicted intervals) and comparisons were performed using univariate logistic regressions. For a given age and level of airflow obstruction, women with COPD had higher BOD scores due to more pronounced dyspn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
2
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 15 publications
3
28
2
2
Order By: Relevance
“…Despite increased diagnosis of COPD in women and the different disease expression,[44] our data failed to find an association with follow-up time. This is probably because the majority of our patients were males and peak COPD prevalence rates in women have yet to be seen.…”
Section: Discussioncontrasting
confidence: 67%
“…Despite increased diagnosis of COPD in women and the different disease expression,[44] our data failed to find an association with follow-up time. This is probably because the majority of our patients were males and peak COPD prevalence rates in women have yet to be seen.…”
Section: Discussioncontrasting
confidence: 67%
“…These observations are in alignment with earlier published literature. 15,16,[28][29][30][31] Depression and anxiety are among the strongest predictors of impaired quality of life, 32 and anxiety among COPD patients can lead to the vicious cycle of breathlessness and anxiety known as "dyspnea-anxiety-dyspnea cycle," which means that patients' emotional response to breathlessness result in intensification of their perception of breathlessness. 33 Hence, it is very important for healthcare professionals to be knowledgeable of and take into account gender differences regarding comorbidities when managing patients with COPD.…”
Section: Discussionmentioning
confidence: 99%
“…Dyspnoea appears strongly associated with depression in women [34][35][36][37]. In France, a working group studying a real-life COPD patient population showed that, for a given age and level of airflow obstruction, women have a higher BODE index (body mass index, airflow obstruction, dyspnoea and exercise capacity) due to a lower body mass index and more pronounced dyspnoea, suggesting a poorer overall prognosis [38]. Considering the pulmonary hypertension phenotype in COPD, it is equally present in both sexes as shown by the ASPIRE register, whereas there is a female predominance in pulmonary hypertension in group one [39].…”
Section: Epidemiology Of Copd In Womenmentioning
confidence: 99%